Behavioral Analysis of the Weaver Ants (Oecophylla smaragdina) on Bougenville Trees in Temon Kulonprogo - Elsa Aprilia Ningrum; Hayyuning Lathi; Tantri Ayu Ratnasari; Yunita Fera Rahmawati (Jurnal Sains Dasar, 2023)
The behavioral analysis of weaver ants (Oecophylla smaragdina) was carried out by observing the behavior of weaver ants found on the Bougenville tree located at the researcher's house in the Temon area, Kulonprogo. Observations were made using the Ad Libitum, Scan Sampling, and Behavioral Sampling methods on the behavior of weaver ants (Oecophylla smaragdina) with each method being repeated three times. The purpose of this study was to determine the specific behavior of weaver ants (Oecophylla smaragdina) for 24 hours. The results showed that there were differences in the activity of weaver ants in the morning, afternoon, and evening. In the morning the weaver ants have not done much activity, so the observations show that 44% of weaver ants' activity is inactive. Other activities observed in the morning were walking (28%), communication (20%), and colonizing (8%). During the day observed transport (20.7%), walking into the nest (19%), grooming (17.2%), silence (16.4%), communication (11.2%), walking out of the nest ( 8.6%), colonies (5.2%), and nests (1.7%). In the afternoon the activity of weaver ants was observed to be less than during the day. The most observed activities were silence (36.4%), walking into the nest (24.5%), communication (14.5%), colonizing (11.8%), grooming (9.1%), and entering nest 3.6%. Silent activity is the most observed activity in this observation, resting activity is an important activity carried out by individuals after eating activities.